Lactic acid bacteria additives effectively regulate nitrogen compounds and related bacterial communities in silage infected with leaf spot disease - Zhang, Xiaolong; Meng, Yuanyan; Xu, Liuxing (Frontiers in Animal Science, 2025)
Leaf spot is a widespread disease that poses a severe challenge to the forage industry. Lactic acid bacteria (LAB) additives inhibit the growth of harmful bacteria through mechanisms such as competitive exclusion and the production of antimicrobial substances, thereby improving the fermentation environment. The aim of this study was to explore the effects of LAB on the regulation of nitrogen compounds and related bacterial communities in silage infected with leaf spot disease. The experiments included two forage types (Italian ryegrass [IR] and oat), three additives (deionized water [control, CK], Lactobacillus plantarum YM3, and Lactobacillus rhamnosus HT1), and four ensiling periods (0, 15, 30, and 60 d). Ammonia-N concentration and LAB numbers increased with increasing ensiling time. The ammonia-N concentration of IR was significantly lower than that of oat (P < 0.05). The aminopeptidase activity of CK silage (10.5 units h-1 g-1 dry matter [DM]) was higher than that of YM3 (7.19 units h-1 g-1 DM) and HT1 silages (7.07 units h-1 g-1 DM) (P < 0.05). The YM3 silage (94.5 g kg-1 DM) had a higher lactic acid concentration than that of CK (69.5 g kg-1 DM) and HT1 silages (83.3 g kg-1 DM) (P < 0.05). Among the 12 environmental factors analyzed, pH (R2 = 0.1171, P = 0.0113) and ammonia-N (R2 = 0.076, P = 0.0436) had the greatest influence on bacterial relative abundance. The normalized shuffle test index demonstrated a significant impact on microbial stability, with differences observed under varying treatment conditions (IR > oat, CK > HT1 > YM3, and ES60 > ES15 > ES30 (P < 0.05)). In conclusion, oat silage exhibited better fermentation quality and bacterial stability than that of IR. Extending the ensiling time significantly improved the overall fermentation quality of silage. Furthermore, the application of LAB additives, particularly YM3, significantly enhanced the fermentation quality and bacterial stability of silage from forage infected with leaf spot disease.